Maimonides' apostasy according to Muslim and Jewish sources - Mazor, Amir (Journal of Jewish studies, 2019)
The article presents and analyses the different Muslim accounts regarding Maimonides' conversion to Islam and his apostasy, and indicates the similarities between the Muslim accounts and Jewish folk tales about Maimonides. It points out that the same motifs regarding Maimonides that appear in both Muslim and Jewish accounts are interpreted differently by Muslims and Jews. While in the Muslim accounts Maimonides, as a Jew, is depicted as ungrateful, malicious and treacherous, in the Jewish legends Maimonides is presented as a wily, clever and superior Jew, who mocks the Muslims. The article suggests that the motives for Maimonides' negative depiction derived from Muslim authors' commitment to the Islamic discourse regarding Jews, while the praise of Maimonides in the Jewish tales came in reaction to the Muslim reports, aiming to conceal his conversion.